ALCOHOL ABUSE ENHANCES SYSTEMIC INFLAMMATORY RESPONSE IN PATIENTS AFTER SPONTANEOUS INTRACEREBRAL HAEMORRHAGE - Maya Danovska; Margarita Alexandrova; Dora Peychinska; I. Gencheva (Peytchinski Publishing, 2010)
OBJECTIVE: The role of inflammation in the complex pathophysiology of spontaneous intracerebral hemorrhage (sICH) was studied by assessing the relationship between serum C-reactive protein (CRP) levels and some clinical and neuroradiological parameters. We also aimed to identify the effects of modifiable vascular risk factors on serum CRP levels.PATIENTS: Forty six patients with sICH admitted to the Department of Neurology and Neurosurgery of the Pleven University Hospital, Bulgaria were examined. Serum CRP levels were measured within the first 48 hours of disease onset and analyzed in relation to neurological deficit severity and clinical outcome after sICH. The impact of some vascular risk factors on the inflammatory marker levels was also studied.RESULTS: We found enhanced CRP levels in patients with severe neurological deficit as assessed by the National Institutes of Health Stroke Scale (NIHSS) score. Significantly higher CRP levels were measured in patients with progressive clinical deterioration and worse outcome. Serum CRP levels were also higher in patients with a history of alcohol abuse.CONCLUSIONS: Our results suggest that inflammation plays a crucial role in the development of brain injury after sICH. They show that CRP, a nonspecific inflammatory marker, can serve as an additional diagnostic and prognostic test indicator in the acute stage of sICH thus providing an excellent opportunity for therapeutic interventions while the patient is still in clinic. Patients with a history of systemic alcohol abuse demonstrate stronger inflammatory response indicative for worse prognosis.